2021
DOI: 10.3389/fmed.2021.600879
|View full text |Cite
|
Sign up to set email alerts
|

The Human Microbiome, an Emerging Key-Player in the Sex Gap in Respiratory Diseases

Abstract: The sex gap is well-documented in respiratory diseases such as cystic fibrosis and chronic obstructive pulmonary disease. While the differences between males and females in prevalence, severity and prognosis are well-established, the pathophysiology of the sex difference has been poorly characterized to date. Over the past 10 years, metagenomics-based studies have revealed the presence of a resident microbiome in the respiratory tract and its central role in respiratory disease. The lung microbiome is associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 62 publications
1
10
0
Order By: Relevance
“…Nevertheless, female sex in CF was shown to be a significant risk factor for death; women also acquire P. aeruginosa at an earlier age, as well as several other pathogens such as S. aureus , Haemophilus influenzae , A. xyloxidans , B. cepacia , Aspergillus and nontuberculous mycobacteria [ 20 ]. A wide range of factors have been examined to explain the sex gap in airway diseases [ 21 ]. In a study investigating the impact of inhaled aztreonam on the lung microbiome in CF, males showed a significantly higher Shannon diversity index with lower abundance of P. aeruginosa and increased abundance in other genera, including Streptococcus spp.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, female sex in CF was shown to be a significant risk factor for death; women also acquire P. aeruginosa at an earlier age, as well as several other pathogens such as S. aureus , Haemophilus influenzae , A. xyloxidans , B. cepacia , Aspergillus and nontuberculous mycobacteria [ 20 ]. A wide range of factors have been examined to explain the sex gap in airway diseases [ 21 ]. In a study investigating the impact of inhaled aztreonam on the lung microbiome in CF, males showed a significantly higher Shannon diversity index with lower abundance of P. aeruginosa and increased abundance in other genera, including Streptococcus spp.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first study to have reported a modifying effect of sex on the relationship between asthma and RTIs. The stronger effect of asthma on susceptibility to infections in girls compared with boys in young adulthood could be explained by the differences in airway microbiota ( 36 ), by sex hormones ( 33 ), and/or by different types of immune responses ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that differences in the composition of the airway microbiome of men and women, determined by host factors such as sex hormones, anatomy, and the immune environment, may explain some of the sex differences in the clinical features of COPD. 56 For example, women tend to develop COPD at an earlier age than men, and tend to have better lung function but more dyspnea and more frequent COPD exacerbations than men. 57,58 So far, little has been reported on sex differences in the lung microbiome in COPD.…”
Section: Discussionmentioning
confidence: 99%